About (need) kindness in the employee-supervisor relationship. An attempt to analyze the problem on the border of the humanities and social sciences – selected aspects (Economic and Political Thought, 2022)
In the classical approach to ethics, such categories as: humanity, human attitude towards someone, kindness, education, personal culture or kindness are mixed. One of the specific - from the social and economic point of view - is the employee-supervisor relationship. The aim of the article was an attempt to answer the following research questions: to what extent kindness as an ethical category can or does affect the employee-supervisor relationship and whether and wherever kindness has its place in the perspective of the applicable labor law and in the aspect of social sciences in the field of human resource management. The answer to this question, based on the analysis of selected areas of labor law as well as in relation to selected contemporaryphilosophical trends, is positive. However, there remain debatable issues in the area of other ethics (e.g. utilitarianism) and economics (the profit-to-interpersonal relationship in an enterprise).
Keywords: ethics, human resource management, kindness, employee, supervisor, labor law